Diversity of Rock-Inhabiting Fungi in Tarragona Province, Spain - Angie Paola Sastoque; José Francisco Cano-Lira; Alberto Miguel Stchigel (Journal of Fungi, 2024)
Rock-inhabiting fungi (RIF) are usually extremely tolerant or extremophilic, as they can survive on natural and artificial rocks despite being exposed to stressful conditions. RIF have serious negative effects on the appearance and cohesion of rocky substrates, causing the alteration and decomposition of building materials, but also on human and animal health, as they can act as opportunistic pathogens. Their identification is therefore of great importance, especially in urban areas. In the present study, culturing techniques for isolating fungi, and a polyphasic taxonomic approach to their identification, were used to assess the diversity of micromycetes that darken the surfaces of buildings in various villages and cities in Tarragona Province (Spain). Sixty-four species of RIF belonging to forty-one genera were identified, including a new genus (Coccodomyces) and the following six new fungal species: Coccodomyces pleiosporus, Exophiala caementiphila, Exophiala multiformis, Neocatenulostroma spinulosum, Neodevriesia longicatenispora, and Paradevriesia holothallica. Thus, we have established that building materials are ecological niches where a high biodiversity of RIF can develop.